ANALISIS PEMENUHAN HAK KELOMPOK RENTAN DALAM SUDUT PANDANG DISABILITAS DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Hidayat, Azis Imam (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study analyzes the fulfillment of the rights of vulnerable groups, particularly individuals with disabilities, within correctional institutions. The urgency of this research stems from the lack of adequate attention and resources allocated to this demographic, which often leads to violations of their rights. A qualitative research method was employed, involving interviews and observations within selected correctional facilities. The findings indicate significant gaps in the provision of necessary services and support for disabled inmates, highlighting systemic issues that hinder their rehabilitation and reintegration into society. This research underscores the need for policy reforms to ensure that the rights of disabled individuals in correctional settings are recognized and upheld.Keywordsvulnerable groups; disability rights; correctional institutions; policy reform.